2018
DOI: 10.1299/jtst.2018jtst0035
|View full text |Cite
|
Sign up to set email alerts
|

Research on coupled heat transfer of film cooling in LOX/GH<sub>2</sub> thrust chambers

Abstract: To better understand the performance of gaseous film cooling near the injector region in the LOX/GH 2 thrust chambers, a methodology is employed to simulate the coupled heat transfer of the film cooling in thrust chambers with regenerative cooling. The conjugated flow and heat transfer behaviors of film coolant, hot gas, cooling channels and regenerative coolant are numerically investigated. A three-dimensional non-adiabatic flamelet model using real gas equation of state is developed to solve the combustion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The study showed that the growth rate of the shear layer between the hot and the cold streams is significantly influenced by compressibility. A recent numerical study by Xiang and Sun [ 19 ] incorporating the effect of fuel injection and combustion on film cooling showed that vortex structures formed in the regions close to the injectors enhance the mixing of the coolant with the mainstream and thereby adversely impact the cooling effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that the growth rate of the shear layer between the hot and the cold streams is significantly influenced by compressibility. A recent numerical study by Xiang and Sun [ 19 ] incorporating the effect of fuel injection and combustion on film cooling showed that vortex structures formed in the regions close to the injectors enhance the mixing of the coolant with the mainstream and thereby adversely impact the cooling effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of film cooling, Shine's research [15][16][17] showed that the injector structure has an important impact on film cooling, and there is an optimal blowing ratio for a given geometry. Xiang et al [18][19][20] studied the effect of gas film cooling holes with different angles on the cooling effect in rocket engines with various propellant combinations through experiments and numerical simulation. Fu et al [20] developed a droplet/wall impact model which performed better than the O'Rourke and Amsden model.…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of applying the fluid nozzle throat to solid rocket motors was verified. In order to deeply study the performance of film cooling near the ejector area in the LOX/GH2 thrust chamber, Xiang et al 23 studied the conjugate flow and heat transfer behavior of film coolant, hot gas, cooling channel and regeneration coolant through numerical simulation, and established the three-dimensional non-adiabatic flamelet model which used the real gas state equation. Wang et al 24 conducted numerical simulations to study the working characteristics of axisymmetric divergent bypass dual-throat nozzles.…”
Section: Introductionmentioning
confidence: 99%